Pelatihan Digitalisasi dan Pemasaran Dalam Mendukung Peluang dan Menghadapi Tantangan bagi UMKM - Tiarapuspa; Firdayetti, Firdayetti; Dian Oktaviani; Ega Ayu Aprilia; Herliana Febrianti; Nisma Faturahmi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2024)
This training aims to analyze the application of marketing digitalization to Micro, Small and Medium Enterprises (MSMEs) run by housewives and identify the obstacles and challenges faced by MSMEs in implementing digital marketing. The research methodology uses an action research approach involving the PKK Seruni RT 017 in Mangunjaya Village, Bekasi Regency. The research steps include problem identification, action planning, action implementation, observation and reflection, as well as evaluation and planning for the next cycle. Data were obtained through interviews and observations of 10 respondents who were members of the PKK Seruni RT 017 group. The results showed that there was a significant increase in the application of marketing digitalization after the training. Most MSMEs that previously did not use social media or online platforms started using Instagram as a marketing platform. MSMEs are expected to receive advanced training regarding content creation and customer interaction management. Continuous support and assistance is also needed to assist MSMEs in implementing digital marketing strategies effectively. In addition, it is necessary to develop and implement management and promotion strategies that can overcome existing weaknesses. MSMEs also need to continue to maintain their strengths, such as product quality, competitive prices, and customer service.